Here to stay, here to fight : a Race today anthology - Field, Paul, 1971-; Bunce, R. E. R. (Robin E. R.); Howe, Leila Hassan, 1948-; Peacock, Margaret (London : Pluto Press, 2019)
A unique anthology of Race Today (1973-88), featuring original contributions from C.L.R. James, Linton Kwesi Johnson and Darcus Howe.
Cover; Contents; List of Figures; Acknowledgements; Introduction -- Leila Hassan, Robin Bunce and Paul Field; 1. Race Today and British Politics; 2. Black Youth in Revolt; 3. Sex, Race and Class; 4. Asian Communities, Asian Workers and Race Today; 5. Challenging British (In)Justice; 6. 'Creation for Liberation': Race Today and Culture; 7. For Black and Third World Liberation; 8. Legacies; Notes on Contributors; Index
Includes index.
Online resource, title from digital title page (Ebook Central, viewed on June 22, 2020).
JSTOR
Keywords: Race relations; Civil rights; Race; Race discrimination; Ethnic relations; Racial Groups; Relations raciales; Race; Discrimination raciale; Relations interethniques; racial discrimination; race (group of people); POLITICAL SCIENCE -- Political Process -- Political Advocacy; Race relations; Civil rights; Ethnic relations; Race; Race discrimination